Pengembangan Soal Setara TIMSS untuk Mengukur Kemampuan Penalaran Matematika Siswa dalam Konten Geometri - Hafizhah, Hafizhah; Amry, Zul (CV. Ulil Albab Corp, 2024)
This research aims to produce the development of TIMSS equivalent questions to measure students' mathematical reasoning abilities in geometry content that are valid, practical and effective and to describe students' mathematical reasoning abilities in solving TIMSS equivalent questions developed in geometry content. This research is a formative evaluation type of development research with two stages, namely the preliminary stage (preparation stage) and the prototyping stage using a formative evaluation flow consisting of self evaluation, prototyping (expert reviews, one-to-one and small group), and field test. The instruments used were a description test with 7 questions, a response questionnaire from students, teachers and lecturers. The results of this research indicate that TIMSS-equivalent questions have been successfully developed to measure students' mathematical reasoning abilities in quality geometry content as seen from: (1) Validation by experts was declared valid because the three validators stated